Manganese-Based Nanotheranostics for Magnetic Resonance Imaging-Mediated Precise Cancer Management - Du R; Zhao Z; Cui J; Li Y (International Journal of Nanomedicine, 2023)
Ruochen Du,1 Ziwei Zhao,2,* Jing Cui,3,* Yanan Li2 1Department of Laboratory Animal Center, Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China; 2College of Medical Imaging, Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China; 3College of Public Health, Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanan Li, College of Medical Imaging, Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China, Email liyanan0213@sxmu.edu.cnAbstract: Manganese (Mn)-based magnetic resonance imaging (MRI) has become a competitive imaging modality for cancer diagnosis due to its advantages of non-invasiveness, high resolution and excellent biocompatibility. In recent years, a variety of Mn contrast agents based on different material systems have been synthesized, and a series of multi-purpose Mn nanocomposites have also emerged, showing satisfactory relaxation efficiency and MRI performance thus possess the transformation and application value in MRI-synergized cancer diagnosis and treatment. This tutorial review starts from the classification and properties of Mn-based nanomaterials, and then summarizes various preparation and functionalization strategies of nanosized Mn contrast agents, especially focuses on the latest progress of Mn contrast agents in MRI-synergized precise cancer theranostics. In addition, present review also discusses the current clinical transformation obstacles such as unclear molecular mechanisms, potential nanotoxicity, and scale production constraints. This paper provides evidence-based recommendations about the future prospects of multifunctional nanoplatforms, as well as technical guidance and panoramic expectations for the design of clinically meaningful cancer management programs.Keywords: manganese, magnetic resonance imaging, precise diagnosis, targeted therapy, malignant tumor